Identifying creative thinking skills in subject matter bio-chemistry - M. Dwi Wiwik Ernawati; Damris Muhammad; Asrial Asrial; Muhaimin Muhaimin (International Journal of Evaluation and Research in Education (IJERE), 2019)
Creative thinking is needed in 21st century learning. This quantitative study aimed to determine whether chemistry education students at Universitas Jambi have the initial ability of creative thinking. The type of research that is used is a research design survey that is strengthened by the results of interviews to support the results of quantitative data. Where the number of all samples from this study was 188 college students with details of 140 female and 48 male college students from 4th semester chemistry education students who were taken based on purposive sampling technique. Data were then analyzed using SPSS 21 application to find descriptive statistics in the form of mean, median, min, max, and category. From the results of the analysis conducted, it was found that there were students' creative thinking abilities in chemistry subjects in bio-chemical material indicated by sensitivity indicators which had a good category of 44.7% (84 of 188), fluency indicators had a good category of 41.5% (78 of 188), the flexibility indicator has a good category of 40.4% (76 of 188), the originality indicator has a category of 43.1% (81 of 188), and the elaboration indicator has a category of 39.4% (74 of 188).